2013
DOI: 10.1016/j.jpain.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Axonal Regeneration and Swellings in Intraepidermal Nerve Fibers Characterize Painful Phenotypes of Diabetic Neuropathy

Abstract: We examined changes in intraepidermal nerve fibers (IENFs) to differentiate patients with diabetic neuropathy (DN) and neuropathic pain (DN-P) from those with DN without pain (DN-NOP). Punch skin biopsies were collected from the proximal thigh (PT) and distal leg (DL) of normal subjects (NS), patients with type 2 diabetes without evidence of DN (DM), or DN-P and DN-NOP patients. Protein gene product 9.5 (PGP) immunohistochemistry was used to quantify total IENF, and growth associated protein 43 (GAP43) for reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 23 publications
10
78
2
1
Order By: Relevance
“…It is possible that our observed larger mitochondrial signals could be composed of clusters of smaller, potentially dysfunctional mitochondria that have gone through aberrant fission, or of larger predegenerative, swollen mitochondria 4043. In support of this, recent work from our group observed axonal swelling associated with IENFs of patients with diabetic neuropathic pain 44. It is possible that mitochondrial and axonal swellings are associated with changes in sensory nerve function.…”
Section: Discussionsupporting
confidence: 68%
“…It is possible that our observed larger mitochondrial signals could be composed of clusters of smaller, potentially dysfunctional mitochondria that have gone through aberrant fission, or of larger predegenerative, swollen mitochondria 4043. In support of this, recent work from our group observed axonal swelling associated with IENFs of patients with diabetic neuropathic pain 44. It is possible that mitochondrial and axonal swellings are associated with changes in sensory nerve function.…”
Section: Discussionsupporting
confidence: 68%
“…The main symptoms of diabetic neuropathy are tingling and numbness in the distal extremities sometimes accompanied by burning pain (Argoff et al 2006). Animal and human histochemical studies indicate that diabetes can cause dieback of PNS epidermal endings (Sorensen et al 2006; Cheng et al 2013; Cheung et al 2015; Ebenezer and Polydefkis 2014), an outcome that may not be related to pain (Sorensen et al 2006). Also, in studies where diabetes is modeled in animals, the development of ectopic activity in DRG neurons (Khan et al 2002; Serra et al 2012) has been demonstrated.…”
Section: 8 Ampk: Diabetic Neuropathy Prevention and Treatmentmentioning
confidence: 99%
“…Upregulation of receptor over time in painful DPN (Pabbidi et al, 2008) Altered ion-channel expression or function Upregulation of expression of voltage gated Na channels 1.3, 1.6, 1.9 Dysregulation of expression of Na channel 1.8 (Craner et al, 2002) Post-translational modification of Na (v) 1.8 by methylglyoxal causing increased excitability (Bierhaus et al, 2012) Upregulation Ca channels, and dysregulation of cellular calcium leading to increased excitability Decreased fiber counts in painful DPN, increased regenerative markers (Quattrini et al, 2007;Cheng et al, 2013) BDNF, brain-derived neurotrophic factor; Ca, calcium; IENFD, intraepidermal nerve fiber density; NGF, nerve growth factor; PDPN, painful diabetic peripheral neuropathy; PLDPN, painless diabetic peripheral neuropathy; STZ, streptozotocin; TRPV1, transient receptor potential cation channel subfamily V member 1.…”
Section: Trpv1mentioning
confidence: 99%